O‘ZBEK TILIDA IMLO QOIDALARINI O‘RGATISHNING ZAMONAVIY YONDASHUVLARI (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2025)
This article analyzes modern approaches to teaching spelling rules in the Uzbek language. In particular, it highlights the role of innovative pedagogical technologies, interactive methods, and digital resources in improving students’ literacy skills. A comparative analysis of traditional and modern methods of teaching orthography is provided, focusing on effective strategies for developing and reinforcing spelling competencies. The study also examines the impact of online platforms, multimedia tools, electronic textbooks, and testing systems on the learning process. The article offers practical recommendations for implementing new approaches aimed at enhancing the quality of teaching spelling rules.